Quality evaluation of snack produced from black pepper (Piper nigrum L.), plantain (Musa paradisiaca L.) and tigernut (Cyperus esculentus L.) flour blends - Adelekan, E.O.; Adegunwa, M.O.; Adebowale, A.A.; Bakare, H.A.; Alamu, Emmanuel Oladeji (Informa UK Limited, 2019)
Chinchin has been identified to be one the favoured food items and a much-relished pastry which has been eaten as dessert or snack. This study aimed at evaluating the nutritional quality and organoleptic properties of black-pepper enriched Chinchin produced from plantain-tigernuts composite flour. Matured plantains (Musa paradisiaca), tigernuts (Cyperus esculentus) and black pepper were processed into flour. Chinchin was processed from different blends of plantain and tigernuts composite flour at the ratio of 100:0, 70:30, 60:40, 50:50, 40:60, 30:70, and 0:100 for plantain and tigernuts respectively. Five percent (5%) black pepper spice was added to each of the samples for Chinchin production. Proximate, mineral and vitamin compositions were determined using standard methods. The results of proximate composition of the different snack samples showed significant differences (P<0.05) with values ranging from 6.50-10.00%, 4.45-6.75%, 2.25-32.75, 1.33-2.00%, 3.50-6.13% and 46.07-78.48% for moisture, protein, fat, ash, crude fibre and carbohydrate contents respectively. There was significant difference (p < 0.05) in the minerals and vitamins contents, and organoleptic properties of the black pepper chinchin samples. In conclusion, chinchin of improved and acceptable nutritional and organoleptic properties could be obtained using plantain-tigernuts composite flour and black pepper spice for improved nutrition. This product could add to range of snacks available for those with special dietary needs.